Products and Mappings of Intuitionistic Fuzzy T0, T1 and T2-Spaces - Ahmed, Estiaq; Hossain, MS; Ali, DM (Journal of Bangladesh Academy of Sciences, 2015)
The basic concepts of the theory of intuitionistic fuzzy topological spaces have been defined by some workers. In this paper, the product and mappings of T0, T1 and T2-spaces have been studied. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 223-231, 2015